HYPOCALCAEMIA - CASE REPORT - Tina Svetlik; Klemen Dovč; Primož Kotnik (The Society for Children with Metabolic Disorders, 2022)
Hypocalcaemia is a common disorder of calcium and phosphate metabolism in children, especially in newborns. It is often asymptomatic; clinical signs and symptoms are dependent on the age of the child. The primary care physician can confirm hypocalcaemia in the child with a suspicious clinical picture and clinically stabilise the child. Further laboratory and imaging diagnostics should be performed at the secondary and most often the tertiary level of medical care. In the article, the case of a girl with clinically manifested hypocalcaemia, caused by primary hypoparathyroidism as a consequence of autoimmune polyglandular syndrome type 1, is presented.